A new species of Arisaema (Araceae) from Vietnam - Van, Hong Thien; Nguyen-Phi, Nga; Luu, Hong Truong (Phytotaxa, 2016)
Arisaema langbiangense (Araceae) is described and illustrated as a new species from Langbiang Mountain, Bidoup-Nui Ba National Park, Lac Duong District, Lam Dong Province, Vietnam. A morphological comparison between the new species and its closest congeners and a key to all known species of Arisaema sect. Anomala in Vietnam are given.